Identification of Ethnoscience in the Madura Keris as a Source for Learning Science in Junior High Schools - Annuria Auliya Rahma; Mochammad Yasir; Hartiningsih, Try (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2023)
This study aims to identify the ethnoscience found in the Madura Keris which can be used as a source of learning natural sciences for junior high schools. The time of research was in July-September at the Aeng Tong Tong village, Sumenep. Methods of data collection using the method of observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, conclusions and verification. There is data triangulation using the triangulation method by matching the interview results with the observation sheet. The results of the data findings were then verified by the SMP science teacher. The research results show that: 1) the results of the ethnoscience study can be seen in the tools and materials used, the manufacturing process, community techniques in caring for and conserving Madurese keris in the local community; 2) the results of the ethnoscience study are connected and closely related to the science concept material for grade 7 & grade 8 independent curriculum, namely elements, compounds, mixtures of materials, temperature, heat and changes in form. These results show that the Madurese keris can be used as a source of science learning for junior high schools.